Psychology and Speed Skating: The New Frontier of Performance. (Sport and Exercise Psychology, 2025)
The article explores the psychological and physical dynamics of speed skating and short track, two Olympic disciplines united by speed but distinguished by their specific dynamics and competitive context.Speed skating requires emotional self-regulation and resilience to frustration, while short track demands risk tolerance, reactivity, and arousal management.The mental dimension plays a crucial role in performance, of equal importance to physical skills.Although limited, recent studies highlight distinct personality profiles, with temperamental traits related to impulsivity, persistence, and sensation seeking.The central role of self-efficacy in achieving athletic success is emphasized, along with the value of tailored psychological interventions.The article proposes a multidimensional approach, promoting a sports culture that recognizes psychological well-being as a foundation for performance and personal development.
Keywords: speed skating; short track; self efficacy; arousal; impulsivity